Current and Potential Treatments for Reducing Campylobacter Colonization in Animal Hosts and Disease in Humans - Johnson, Tylor J.; Shank, Janette M.; Johnson, Jeremiah G. (Frontiers in Microbiology, 2017)
Campylobacter jejuni is the leading cause of bacteria-derived gastroenteritis worldwide. In the developed world, Campylobacter is usually acquired by consuming under-cooked poultry, while in the developing world it is often obtained through drinking contaminated water. Once consumed, the bacteria adhere to the intestinal epithelium or mucus layer, causing toxin-mediated inhibition of fluid reabsorption from the intestine and invasion-induced inflammation and diarrhea. Traditionally, severe or prolonged cases of campylobacteriosis have been treated with antibiotics; however, overuse of these antibiotics has led to the emergence of antibiotic-resistant strains. As the incidence of antibiotic resistance, emergence of post-infectious diseases, and economic burden associated with Campylobacter increases, it is becoming urgent that novel treatments are developed to reduce Campylobacter numbers in commercial poultry and campylobacteriosis in humans. The purpose of this review is to provide the current status of present and proposed treatments to combat Campylobacter infection in humans and colonization in animal reservoirs. These treatments include anti-Campylobacter compounds, probiotics, bacteriophage, vaccines, and anti-Campylobacter bacteriocins, all of which may be successful at reducing the incidence of campylobacteriosis in humans and/or colonization loads in poultry. In addition to reviewing treatments, we will also address several proposed targets that may be used in future development of novel anti-Campylobacter treatments.